2017
DOI: 10.1080/00071668.2017.1340588
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of bedding materials and elevated platforms on contact dermatitis and plumage cleanliness of commercial broilers and on litter condition in broiler houses

Abstract: 1. Experiment 1, comparing wood shavings and ground straw bedding with peat, was performed on 7 broiler farms over two consecutive batches during the winter season. Experiment 2, assessing the effect of elevated (30 cm) platforms, was conducted in three farms replicated with 6 consecutive batches. 2. Footpad lesions were inspected at slaughter following the Welfare Quality® (WQ) assessment and official programme. Hock lesions, plumage cleanliness and litter condition were assessed using the WQ assessment. Litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 46 publications
4
31
1
4
Order By: Relevance
“…For all treatments, the mean plumage soiling scores were low, as 0 on the ordinal scale (no soiling) was scored most frequently (71% of the scores; data not shown). These low scores are not in-line with a previous study under comparable stocking density conditions, where 99% of birds showed slight soiling irrespective of the litter treatment [ 24 ]. PREV-POS resulted in lower (better) soiling scores compared to PREV-MAT and PREV-SLAT, suggesting that the best strategy to avoid soiling is early access to clean litter that is regularly replaced.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…For all treatments, the mean plumage soiling scores were low, as 0 on the ordinal scale (no soiling) was scored most frequently (71% of the scores; data not shown). These low scores are not in-line with a previous study under comparable stocking density conditions, where 99% of birds showed slight soiling irrespective of the litter treatment [ 24 ]. PREV-POS resulted in lower (better) soiling scores compared to PREV-MAT and PREV-SLAT, suggesting that the best strategy to avoid soiling is early access to clean litter that is regularly replaced.…”
Section: Discussioncontrasting
confidence: 84%
“…Every four days, the mats were removed from the pen, cleaned, and refilled with the disinfectant solution. The second novel flooring treatment entailed the provision of the MAT treatment (mat plus disinfectant solution), with the additional provision of a black plastic slatted floor (SLAT; Figure 1 b) (60 × 120 cm, DURA-SLAT ® Black Poultry & Kennel Flooring, Southwest Agri-Plastics Inc. Addison, TX, USA), placed on top of the litter but not elevated from the ground, as commonly done for laying hens and broiler breeders [ 24 ]. The mat was placed on top of the slatted floor, and both were placed in the back middle of the pen under the drinker, provided on day 1 (PREV) or day 29 (REM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies showed results with a higher plumage cleanliness for animals kept on a perforated flooring system compared to litter flooring ( Akpobome and Fanguy, 1992 , Almeida et al., 2017 , Li et al., 2017 , Çavuşoğlu et al., 2018 , Çavuşoğlu and Petek, 2019 ). As reported by Kaukonen et al. (2017) , the use of perforated platforms (10% of the floor area) had no effect on plumage cleanliness.…”
Section: Discussionsupporting
confidence: 51%
“…Epidemiological surveys linked the increased prevalence of the condition to various production aspects, including increased population density, slaughter at a higher age and bigger male to female ratio in the flock (Bruce et al 1990). The appearance of contact dermatitis lesions has also been linked to bad litter conditions, particularly when it occurred suddenly or within a short period of time (McIlroy et al 1987;Bruce et al 1990;Kaukonen et al 2017). Lesions similar to those observed in broiler chickens were encountered in turkeys, housed on wet litter (Martland 1984).…”
Section: Introductionmentioning
confidence: 99%